Influence of Orbital Forcing on the Snowball Earth Deglaciation - Jiacheng Wu; Yonggang Liu (Geophysical Research Letters)
Abstract Neoproterozoic snowball Earth events lasted for multiple million years, experiencing many orbital cycles. Here we investigate whether the deglaciation of these events would be triggered more easily at certain orbital configurations than others, by using an atmosphere‐land model that considers meltpond formation on land ice. Results show that the threshold concentration of atmospheric CO2 (pCO2) required for deglaciation can vary from 6 to 10 × 104 ppmv under different orbital forcings. The threshold pCO2 decreases with the equatorial maximum monthly insolation (EMMI), which is affected most by the eccentricity and secondarily by obliquity. Therefore, we conclude that the snowball Earth deglaciation likely occurred when the eccentricity was high and obliquity was low. Compared to previous estimate that used present‐day orbital configuration which has a minimal eccentricity, the duration of snowball Earth events would likely be much shorter when the influence of orbital variations are considered.